Correlation Between Covid-19, Anxiety and Work Values Among University Students - Marimuyhu, Nagatheesan V; Mariamdaran Chetiyar, Saralah Devi (Journal of Mental Health and Social Rehabilitation, 2024)
There is a lot of nature in career choice decisions and other spheres of life due to global shifts in available career opportunities that occurred after the 2020 recession due to the COVID-19 outbreak. The purpose of this study is to understand how students’ work attitude and professional orientations have been influenced by anxiety and the COVID-19 pandemic. To achieve this, it will be necessary to employ a quantitative research method as detailed below. Consequently, the hypothesis that will inform this study regarding the effect of anxiety and the pandemic influence on work values decisions. The outcomes will contribute to information about the consequences of fear and the epidemic on work values and career choices among college students. Some of the recommendations of the study will be in the form of recommendation to policymakers, university administration as well as the career counsellors